2014
DOI: 10.1007/s00125-014-3375-9
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro-brain natriuretic peptide and risk of cardiovascular events in older patients with type 2 diabetes: the Edinburgh Type 2 Diabetes Study

Abstract: Aims/hypothesis The aim of this study was to investigate the association of N-terminal pro-brain natriuretic peptide (NTproBNP) with traditional cardiovascular risk factors and incident cardiovascular events in older people with type 2 diabetes. Methods In the prospective phase of the Edinburgh Type 2 Diabetes Study, 1066 men and women aged 60 to 75 years with type 2 diabetes mellitus were followed for 4 years; 112 participants had an incident cardiovascular event. At baseline, cardiovascular risk factors, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…13,14 Notably, NT-proBNP only predicted CV events in 7 subjects with established CVD in the present study, irrespective of diabetes status. Other studies have identified elevated NT-proBNP as a CV risk factor in subjects with T2DM, 15 but to our knowledge it has previously not been shown that this primarily is the case for T2DM subjects with prevalent CVD. Subjects without diabetes that suffered a new event had increased carotid bulb IMT at baseline, but there was no difference in CCA IMT, total carotid plaque area or ABPI.…”
Section: Discussionmentioning
confidence: 61%
“…13,14 Notably, NT-proBNP only predicted CV events in 7 subjects with established CVD in the present study, irrespective of diabetes status. Other studies have identified elevated NT-proBNP as a CV risk factor in subjects with T2DM, 15 but to our knowledge it has previously not been shown that this primarily is the case for T2DM subjects with prevalent CVD. Subjects without diabetes that suffered a new event had increased carotid bulb IMT at baseline, but there was no difference in CCA IMT, total carotid plaque area or ABPI.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to established risk factors, several biomarkers associated with atherosclerosis, inflammation and congestive heart failure [6][7][8][9][10][11] have recently been proposed to improve risk stratification in type 2 diabetes mellitus patients. Promising data have been obtained using biomarkers associated with the closely interlinked processes of atherosclerosis and low-grade systemic inflammation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although very few risk scores have included HbA1c in their risk prediction algorithm, even fewer have comprehensively evaluated and compared a panel of traditional and non‐traditional biomarkers of hyperglycaemia, cardiac damage, kidney filtration, liver function or inflammation . The biomarkers evaluated in the present study were selected because they are markers of physiological damage in the pathway to the clinical endpoints that we included, and have been associated with increased risk of complications in people with diabetes . Our model extends the findings of a previous ARIC study that developed a risk score for 10‐year prediction of a single endpoint of CHD in people with diabetes.…”
Section: Discussionmentioning
confidence: 99%